The Impact of Employee Engagement on Work Performance: Observational Study In The Human Capital Division of PT KPI RU III - Silitonga, Nadia Angelina; Almigo, Nuszep (Institut Teknologi dan Bisnis Asia Malang, 2025)
Purpose: This study examines the impact of employee engagement on work performance within the Human Capital Division of PT KPI RU III Palembang, focusing on emotional, cognitive, and behavioral engagement as drivers of productivity and organizational commitment in the energy sector. Method: Using participatory observation during an internship, data were collected through direct observation of employee interactions, work behavior, and task responses, analyzed contextually to understand engagement dynamics. Practical Applications: Findings support HR strategies by emphasizing psychological safety, supportive leadership, and employee participation to enhance engagement, teamwork, and adaptability, particularly during digital transformation. Conclusion: Employee engagement significantly improves performance, evidenced by discipline, enthusiasm, and teamwork. However, high workloads and limited decision-making involvement remain challenges. Strengthening engagement fosters sustainable performance and organizational success.